Transver ruínas: narrativas possíveis a partir de experimentações - Remígio, Suzane Kely Dias Sousa (2023)
The text presents the research process in Poetics of Creation and Thought in Arts, which aimed to analyze, experiment and reflect on actions carried out in ruins of houses (near Avenida Borges de Melo), at Fortaleza, between 2020 and 2023. How can closer relations with this place arise? It was possible to transver/see through the ruins (from a world perspective by Manoel de Barros). The ruins of these houses were seen as an open field, a booster for the imagination to germinate. The activities carried out included experimenting with these spaces, apprehending the aesthetics of these ruins so that a way of reinventing them could be developed, based on the collected data (photos, videos, audios, drawings) and my creative process (which arises from them), proposing thus, a rewriting that can reimagine them. The narratives that emerged from these activities culminated in this dissertation. The work developed into an art research method based on the “Process Critique”, which Cecilia Salles discusses. This research can be associated with an unusual architectural design of ruins. Each textual part was thought of as decomposed domestic environments (living room, kitchen, bedroom...) and the relationships we can have with them. In this way, the text was elaborated as an exploratory walk through the ruin of a house. This investigation presented different understandings about what was captured from the ruins and from myself, based on artistic creation and reflection on the work of theorists (Gaston Bachelard, Juhanni Pallasmaa, Francesco Careri, Walter Benjamim, Bruno Zevi, among others.) and artists (Íris Helena, Beatriz Rodrigues, Rafael Martins, Thiago Florencio, Paulo Nazareth, Grupo Poro, Yuri Firmeza, Brígida Baltar...) with whom I found dialogue. Literature was also a resource summoned in the composition of text, because I believe that writers (mainly Manoel de Barros), sometimes better translate what I feel or even awaken my sensitivity within the work. With the actions taken, I learned to accept the changes in routes that every field visit offers, one of them was dealing with the pandemic, another was to assume a less passive and more active posture inside the ruined houses. There were a total of six actions: visit to the ruins with data collection, installation of a hammock, creation of a model, elaboration and collage of lambe (Ephemeral), photomontage and exhibition on site. As a result of this project, I brought a writing that comprises a reflection on action, composition, creative process and ruin, with a view to approaching this territory of the city, strengthening the importance of the relationship between art and life.